2017
DOI: 10.1093/mnras/stx1473
|View full text |Cite
|
Sign up to set email alerts
|

How supercritical are stellar dynamos, or why do old main-sequence dwarfs not obey gyrochronology?

Abstract: Asteroseismological determinations of stellar ages have shown that old main-sequence dwarfs do not obey gyrochronology. Their rotation is slow compared to young stars but faster than gyrochronology predicts. This can be explained by the presence of a maximum rotation period beyond which the large-scale dynamo switches off and stops providing global magnetic fields necessary for stellar spindown. Assuming this explanation, the excess of stellar dynamo parameters over their marginal values can be estimated for g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
6
28
0
Order By: Relevance
“…Stars with very low activity are "superrotating," i.e., they rotate faster than expected based on their activity level. This is again a clear indication that these stars, notably 16 Cyg A and B (blue q and r symbols), α Cen A (blue k symbol), and KIC 8006161 (blue o symbol), have experienced reduced magnetic braking as a consequence of the large-scale cyclic dynamo having started to shut down (Kitchatinov & Nepomnyashchikh 2017). For 16 Cyg A and B (blue q and r symbols in Figure 10), this has already happened.…”
Section: Dependence On Convection Zone Thicknessmentioning
confidence: 86%
See 1 more Smart Citation
“…Stars with very low activity are "superrotating," i.e., they rotate faster than expected based on their activity level. This is again a clear indication that these stars, notably 16 Cyg A and B (blue q and r symbols), α Cen A (blue k symbol), and KIC 8006161 (blue o symbol), have experienced reduced magnetic braking as a consequence of the large-scale cyclic dynamo having started to shut down (Kitchatinov & Nepomnyashchikh 2017). For 16 Cyg A and B (blue q and r symbols in Figure 10), this has already happened.…”
Section: Dependence On Convection Zone Thicknessmentioning
confidence: 86%
“…cal once the rotation rate drops below a critical rotation rate (Kitchatinov & Nepomnyashchikh 2017). The BV plot for our sample of F and G dwarfs is shown in Figure 4.…”
Section: F and G Dwarfsmentioning
confidence: 99%
“…Scattering in theoretical estimates may be as large as order of magnitudes. The viewpoint of [39] that solar dynamo is just above the excitation threshold is close to our understanding of the situation however it is too far to be unanimously accepted by the community. Of course, some very qualitative scalings for D are possible.…”
Section: Magnetic Configurations Known For Spherical Dynamosmentioning
confidence: 99%
“…Further, there is an upper value in the rotation period for each spectral type (Rengarajan 1984), also see Metcalfe et al (2016). These observations can be explained by the ceased of the large-scale dynamo above a certain rotation period; see discussion in Kitchatinov & Nepomnyashchikh (2017); Cameron & Schüssler (2017). Thus, the solar dynamo is possibly operating not too far from the critical to the dynamo transition.…”
Section: Introductionmentioning
confidence: 80%
“…Three-dimensional numerical simulations (Karak et al 2015b) and mean-field models (Kitchatinov & Olemskoy 2010) showed that a slightly subcritical dynamo is also possible when the initial condition for the magnetic field is strong. On the other hand, explaining the deviation of gyrochronology in dynamo model, Kitchatinov & Nepomnyashchikh (2017) predicted that solar dynamo is about 10% supercritical.…”
Section: Introductionmentioning
confidence: 99%